Quantifying the Effects of Green Waste Compost Application, Water Content and Nitrogen Fertilization on Nitrous Oxide Emissions in 10 Agricultural Soils. Issue 3 (1st May 2013) - Zhu, Xia; Silva, Lucas C.R.; Doane, Timothy A.; Wu, Ning; Horwath, William R.
Abstract : Common management practices, such as the application of green waste compost, soil moisture manipulation, and nitrogen fertilization, affect nitrous oxide (N2 O) emissions from agricultural soils. To expand our understanding of how soils interact with these controls, we studied their effects in 10 agricultural soils. Application of compost slightly increased N2 O emissions in soils with low initial levels of inorganic N and low background emission. For soils in which compost caused a decrease in emission, this decrease was larger than any of the observed increases in the other soils. The five most important factors driving emission across all soils, in order of increasing importance, were native dissolved organic carbon (DOC), treatment‐induced change in DOC, native inorganic N, change in pH, and soil iron (Fe). Notable was the prominence of Fe as a regulator of N2 O emission. In general, compost is a viable amendment, considering the agronomic benefits it provides against the risk of producing a small increase in N2 O emissions. However, if soil properties and conditions are taken into account, management can recognize the potential effect of compost and thereby reduce N2 O emissions from susceptible soils, particularly by avoiding application of compost under wet conditions and together with ammonium fertilizer.